Effectiveness of revascularization of the ulcerated foot in patients with diabetes and peripheral artery disease: a systematic review. (26th January 2016) - Hinchliffe, R. J.; Brownrigg, J. R. W.; Andros, G.; Apelqvist, J.; Boyko, E. J.; Fitridge, R.; Mills, J. L.; Reekers, J.; Shearman, C. P.; Zierler, R. E.; Schaper, N. C.; ,
Abstract: Symptoms or signs of peripheral artery disease (PAD) can be observed in up to 50% of the patients with a diabetic foot ulcer and is a risk factor for poor healing and amputation. In 2012, a multidisciplinary working group of the International Working Group on the Diabetic Foot published a systematic review on the effectiveness of revascularization of the ulcerated foot in patients with diabetes and PAD. This publication is an update of this review and now includes the results of a systematic search for therapies to revascularize the ulcerated foot in patients with diabetes and PAD from 1980 to June 2014. Only clinically relevant outcomes were assessed. The research conformed to the Preferred Reporting Items for Systematic Reviews and Meta‐analyses guidelines, and Scottish Intercollegiate Guidelines Network methodological scores were assigned. A total of 56 articles were eligible for full‐text review. There were no randomized controlled trials, but there were four nonrandomized studies with a control group. The major outcomes following endovascular or open bypass surgery were broadly similar among the studies. Following open surgery, the 1‐year limb salvage rates were a median of 85% (interquartile range of 80–90%), and following endovascular revascularization, these rates were 78% (70–89%). At 1‐year follow‐up, 60% or more of ulcers had healed following revascularization with either open bypass surgery or endovascular techniques. Studies appeared to demonstrate improved rates of limb salvage associated with revascularization compared with the results of conservatively treated patients in the literature. There were insufficient data to recommend one method of revascularization over another. There is a real need for standardized reporting of baseline demographic data, severity of disease and outcome reporting in this group of patients.